A comparative review on European-farmed finfish RNA viruses and their vaccines - Gómez Casado, Eduardo; Estepa, A.; Coll, J. M. (Vaccine, 2011)
The diseases causing the highest ecological and socio-economical impacts in European farmed finfish are produced by RNA viruses. Salmon, trout, sea bream, sea bass, carp and turbot, suffer viral nervous necrosis produced by betanodaviruses (VNNV), infectious pancreatic necrosis produced by aquabirnaviruses (IPNV), viral haemorrhagic septicemia (VHSV) and infectious haematopoietic necrosis (IHNV) produced by novirhabdoviruses, spring viremia of carp produced by vesicular-like rhabdoviruses (SVCV), salmon pancreas disease and trout sleeping disease produced by alphaviruses (SAV) and infectious salmon anaemia produced by isaviruses (ISAV). There are not yet any effective treatments other than destroying all fish in infected farms, avoiding fish movements to and from infected areas and, in some particular cases, vaccination. The comparative study of the molecular characteristics of those RNA viruses and the state of knowledge of their vaccines, point to the development of new DNA vaccines for some RNA viruses, design of new mass delivery methods, maternal transfer of immunity, more extensive crossprotection studies between genotypes, use of safer all-fish plasmid control elements and study of DNA plasmid distribution after vaccination, as some of the major gaps that need urgent filling. In addition, to obtain similar protection levels to those produced by viral infections in survivors, live attenuated and/or some oil-adjuvanted inactivated virus vaccines, molecular adjuvants and/or other viral components (dsRNA or viral proteins interfering with fish defences), might have to be included in new DNA vaccine formulations. Furthermore, to be approved by the corresponding European authorities, fish viral DNA vaccines would also require the study of the persistence in fish of the introduced DNA, their possible impact to the aquatic environment and the acceptance of potential consumers. © 2011 Elsevier Ltd.